Maturation of the Meniscal Collagen Structure Revealed by Polarization-Resolved and Directional Second Harmonic Generation Microscopy - Pinsard, Maxime (Sci Rep, 2019)
We report Polarization-resolved Second Harmonic Generation (P-SHG) and directional SHG (forward and backward, F/B) measurements of equine foetal and adult collagen in meniscus, over large field-of-views using sample-scanning. Large differences of collagen structure and fibril orientation with maturation are revealed, validating the potential for this novel methodology to track such changes in meniscal structure. The foetal menisci had a non-organized and more random collagen fibrillar structure when compared with adult using P-SHG. For the latter, clusters of homogeneous fibril orientation (inter-fibrillar areas) were revealed, separated by thick fibers. F/B SHG showed numerous different features in adults notably, in thick fibers compared to interfibrillar areas, unlike foetal menisci that showed similar patterns for both directions. This work confirms previous studies and improves the understanding of meniscal collagen structure and its maturation, and makes F/B and P-SHG good candidates for future studies aiming at revealing structural modifications to meniscus due to pathologies.